CHALLENGES OF COMPETITION AND FICTITIOUS PRICING REGULATIONS: STRATEGIES AND APPROACHES TO ADDRESS BUSINESS PRACTICESTHAT IS NOT HONEST - Zaenal Aripin; Lili Adi Wibowo; Faisal Matriadi (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
The practice of setting fictitious prices is one of the serious challenges in maintaining healthy competition and protecting consumers in the market. Regulation has a crucial role in overcoming this practice by creating a business environment that is fair, transparent and has integrity. This article discusses the role of regulations in overcoming fictitious pricing practices and the effectiveness of these regulations in minimizing unfair business practices. Through theoretical discussions and case studies, this article highlights several regulatory strategies that can be implemented, including setting clear standards and conditions, transparency in the price setting process, strict supervision and law enforcement, and providing incentives for business actors who comply with the rules. Evaluation of regulatory effectiveness is also discussed, taking into account influencing factors, such as the level of compliance of business actors, the capacity of regulators, and support from various related parties. In conclusion, it is recommended that the government continue to increase efforts in establishing more effective regulations, while strengthening the capacity of regulators. Business actors need to be encouraged to comply with the rules and pay attention to business ethics in their activities. Consumer organizations and the general public can also play a role in providing input and reporting practices that are detrimental to consumers to regulators. With strong cooperation between all relevant parties, it is hoped that a business environment that is fairer, more transparent and with integrity can be created, as well as reducing dishonest business practices such as fictitious pricing.